PENGARUH LAYANAN PRIMA DAN REPUTASI BANK TERHADAP KEPERCAYAAN NASABAH - Nurul Husnah (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Financial institutions have an important role in improving the national economy. Growth in the number of financial institutions will increase competition and require certain characteristics. One of the basic characteristics of banking is having good services, products, services, and reputation. Excellent service is considered as the dominant factor in the success of an organization, while corporate reputation is an important asset to increase competitive advantage, not only in the banking industry but also in other industries.The presence of Bank Syariah Indonesia (BSI) has changed the landscape of Islamic banking in Indonesia, creating two new forces in the Islamic economy. This research was conducted to evaluate the effect of excellent service and reputation of Bank Syariah Indonesia KCP Balikpapan Sepinggan on customer trust. The research approach used is quantitative, with data collection by distributing questionnaires using a Likert scale. The population taken was 5521 customers, and the sample used was 100 respondents, which was determined using the slovin formula. Data analysis was performed using multiple regression method using SPSS Windows version 26.0 software. The results showed that partially (t-test), excellent service has a positive and significant impact on customer trust. The better the service provided, the customer's trust will increase, and vice versa. In addition, the bank's reputation also has a positive and significant influence on customer trust. When a bank's reputation gets better, customer trust in the bank will also increase. Furthermore, based on the simultaneous test (F-test), there is a significant influence between excellent service and bank reputation together on customer trust. The calculated F value obtained is 83.125 with a significance value of 0.000.